Diversifikasi Produk Brownies Tempe di Industri Rumah Tangga “BROWNIESTA” Melalui Introduksi Teknologi Tepat Guna - Siswanti, Siswanti; Ariviani, Setyaningrum; Ishartani, Dwi; Atmaka, Windi; Khasanah, Lia Umi (PRIMA: Journal of Community Empowering and Services, 2022)
A small medium enterprise (SME) of BROWNIESTA produces tempeh brownies products and is located in Pengkok Village, Kedawung District, Sragen Regency. The community service activities in 2020 conducted by the service team of Universitas Sebelas Maret (UNS) were proven to increase the production capacity and quality of tempeh brownies. The COVID-19 pandemic impacted the cessation of BROWNIESTA SMEs’ production activities. Along with the improvement in post-pandemic conditions, product demand is increasing. However, the increase in product demand could not be fully handled by BROWNIESTA SMEs. BROWNIESTA SMEs experienced difficulties, such as inadequate production equipment and lacking marketing techniques. BROWNIESTA SMEs must also be maintained through product innovation, such as steamed tempeh brownies production. Hence, this service activity aims to increase production efficiency and capacity, elevate tempeh brownies diversification, and improve product marketing techniques at BROWNIESTA SMEs. The service activities involved the appropriate technology introduction through the following activities: 1) a stand mixer and steamer introduction; and 2) the training of entrepreneurship, information technology (IT)-based marketing, and direct selling strategies. A stand mixer introduction succeeded in increasing brownies’ production efficiency by preventing the repetition of dough production in each batch. Brownies’ production capacity also increased up to 20-25% products/day. The steamer introduction successfully produced steamed tempeh brownies, thus tempeh brownies diversification was accomplished. Several training activities were proven to increase BROWNIESTA SMEs’ knowledge, especially regarding online marketing, by launching their first Instagram account to improve business activities.